Self-Esteem dan Social Support Pengaruhnya Terhadap Resiliensi Single Parent di Komunitas Motherland - Rahma Fajri, Meitha; Rahayu, Anizar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research is a quantitative study that aims to determine the effect of self-esteem and social support on resilience in single parents. Respondents in this study amounted to 109people in the Motherland Community who were taken with proportionate stratified randomsampling technique. The measuring instrument in this study consists of Resilience Quotionare (RQTest), Self-esteem and Social Support. Based on analysis with simple linear regression using JASP0.18.3. 0 for Windows shows that there is a significant influence with a positive direction betweenself-esteem on resilience (r = 0.551 and p = 0.001 (<0.05)), there is a significant influence with apositive direction between social support on resilience (r = 0.538 and p = 0.001 (<0.05)), there isa significant influence with a positive direction between self-esteem and social support onresilience found the value of (r = 0.620, R2 = 0.384 and p = 0.001 (<0.05)). This proves thatthere is a significant influence with a positive direction between self-esteem and social support onresilience in single parents. Based on the results of the analysis, it was found that self-esteem hasa more dominant contribution of 30.4% compared to social support which is only 8%.